Evaluation and Comparison of Iodine-Based and Biosynthesized Gold Nanoparticles as X-Ray Contrast Agent and Their Effects on Renal Functions in Male Wistar Rats - Paul Ayanlola; Gbadebo Isola; Waidi Saka; Margaret Akinloye; Abraham Aremu; Mustapha Lawal (Iranian Journal of Medical Physics)
Introduction: Gold nanoparticles (AuNPs) have gained significant attention as a promising contrast agent to overcome the challenges of iodine-based contrast agents (ICAs), such as poor contrast, and renal toxicity. However, studies have associated toxicity with AuNPs synthesized through chemical methods, thereby raising concerns regarding the safety of such AuNPs. This study, hereby, compares the performance of iodine-based and biosynthesized AuNPs from the extract of Psidium guajava and Corchorus olitorius as CA on radiographs and renal functions of rats.Material and Methods: 156 rats were grouped into baseline (A), experimental control (B), ICA (C), and two AuNPs groups (D and E). The ICA (Urografin 76%), AuNPs, 8.23±1.03 nm (from P. guajava), and 6.57±1.62 nm (from C. olitorius) were administered to the rats in groups C, D, and E respectively. The rats, excluding group A, were radiographed, and samples of blood and kidney tissue were collected on days 1 and 30 for the assessment of renal functions.Results: The rats injected with the AuNPs showed radiographic contrast with anatomical features better than those without CA and those injected with the ICA. The biochemicals showed a significant decrease in renal functions for the rats injected with the ICA while those injected with the AuNPs protected against nephropathy when compared with those without CA and those injected with ICA.Conclusion: It was revealed that biosynthesized AuNPs can be a suitable replacement for the ICA because of the high atomic number and attenuation properties of gold, the increased surface area of AuNPs, and biocompatibility.